2009
DOI: 10.1007/s00276-009-0498-7
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a safe-zone in open carpal tunnel surgery: a cadaver study

Abstract: Carpal tunnel decompression is one of the most common surgical procedures in hand surgery. Cutaneous innervation of the palm by median and ulnar nerves was evaluated to find a suitable incision preserving cutaneous nerves. A morphometric study was designed to define the safe-zone for mini-open carpal tunnel release. Sixteen fresh-frozen (8 right, 8 left) and 14 formalin-fixed (8 right, 6 left) cadaveric hands were dissected. Anatomy of the palmar cutaneous branch of the median and the ulnar nerve, motor branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Several other reports 27,28 attributed the scar tenderness to injury of the subcutaneous branches of the palmar cutaneous branch of the median nerve, which are routinely cut during the standard open carpal tunnel release. 29,30 As the nerve crosses the antebrachial fascia from one cm to more than 7 cm proximal to the wrist crease, 28,31,32 if the fascial plane is preserved and only the deep layers are cut, the probability of damaging these cutaneous nerves should be reduced, as suggested also by Martin et al 33 In addition, the preservation of the fascia could avoid the thickening of the point of fascial crossing of the palmar cutaneous branch, as highlighted by Tagliafico et al, 32 which could result in nerve distortion and straining. Also, for Rotman and Donovan, 6 retaining the fascial layer directly palmar to the transverse carpal ligament helps to preserve postoperative pinch strength.…”
mentioning
confidence: 98%
“…Several other reports 27,28 attributed the scar tenderness to injury of the subcutaneous branches of the palmar cutaneous branch of the median nerve, which are routinely cut during the standard open carpal tunnel release. 29,30 As the nerve crosses the antebrachial fascia from one cm to more than 7 cm proximal to the wrist crease, 28,31,32 if the fascial plane is preserved and only the deep layers are cut, the probability of damaging these cutaneous nerves should be reduced, as suggested also by Martin et al 33 In addition, the preservation of the fascia could avoid the thickening of the point of fascial crossing of the palmar cutaneous branch, as highlighted by Tagliafico et al, 32 which could result in nerve distortion and straining. Also, for Rotman and Donovan, 6 retaining the fascial layer directly palmar to the transverse carpal ligament helps to preserve postoperative pinch strength.…”
mentioning
confidence: 98%
“…However, we did observe that the PCUN usually traveled over the Guyon canal, as most fibers were found medial to the pisiform bone. Ozcanli et al 13 found the PCUN in 67% of specimens.…”
Section: Discussionmentioning
confidence: 95%
“…These authors identified a PCUN in 42% of dissected limbs and found that 12.5% of these nerves had branches in the vicinity of a typical carpal tunnel release incision. Ozcanli et al 13 found that the mean distal extent of the PCUN from the distal wrist crease was 4.2 mm. Lastly, given that we identified an intimate relationship of the PCUN with the UA, manipulation of this vessel with various procedures may result in sensory loss over the medial palm.…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly important in light of the currently used endoscopic and open techniques that emphasize a minimally invasive approach. 3,11,25,33 While there are many reports on anatomical variations around the carpal tunnel, 12,23,26,41 there is little mention of the median nerve (MN) in the distal forearm as it approaches the wrist. Most figures depict the MN as taking a linear course that parallels the long axis of the forearm (LAF).…”
mentioning
confidence: 99%